To continue or discontinue aspirin? The risk of perioperative complications - Mroczek, Anna; Bałabuszek, Kamil; Radzka, Agnieszka; Fałkowska, Urszula; Pawlicka, Marta; Bednarski, Jerzy (Journal of Education, Health and Sport, 2018)
Acetylsalicylic acid (aspirin) is a noncompetitive irreversible antagonist of the enzyme cyclooxygenase 1 (COX1). This drug is commonly used in prevention of cardiovascular and cerebrovascular events due to inhibition of platelet function. Because of the risk of surgical hemorrhage it is recommended to cessation aspirin intake couple days before the surgical intervention. However, discontinuation of aspirin treatment may results in increased risk of thrombotic events and perioperative complications. Antithrombotic Trialist’s Collaboration proved that low dose of aspirin intake before surgery reduces the risk of nonfatal myocardial infarction by 33%, vascular events by 17% and nonfatal stroke by 25%. However, some studies showed the increased risk of perioperative bleeding in patients continuing aspirin treatment. The position of experts is not unambiguous and there have been doubts about the necessity of discontinuation or continuation this drug before surgery.